2015
DOI: 10.1038/ncomms10047
|View full text |Cite
|
Sign up to set email alerts
|

The epigenomic landscape of African rainforest hunter-gatherers and farmers

Abstract: The genetic history of African populations is increasingly well documented, yet their patterns of epigenomic variation remain uncharacterized. Moreover, the relative impacts of DNA sequence variation and temporal changes in lifestyle and habitat on the human epigenome remain unknown. Here we generate genome-wide genotype and DNA methylation profiles for 362 rainforest hunter-gatherers and sedentary farmers. We find that the current habitat and historical lifestyle of a population have similarly critical impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 68 publications
5
84
0
Order By: Relevance
“…Maud Fagny and colleagues (61) have found that the current habitat and historical lifestyle of a population have similarly critical impacts on the methylome, but the biological functions affected differ strongly. Specifically, the methylation variation associated with recent changes in habitat mostly concerns immune and cellular functions, whereas the variation associated with historical lifestyle affects developmental processes.…”
Section: Epigenetic Reprogrammingmentioning
confidence: 99%
See 2 more Smart Citations
“…Maud Fagny and colleagues (61) have found that the current habitat and historical lifestyle of a population have similarly critical impacts on the methylome, but the biological functions affected differ strongly. Specifically, the methylation variation associated with recent changes in habitat mostly concerns immune and cellular functions, whereas the variation associated with historical lifestyle affects developmental processes.…”
Section: Epigenetic Reprogrammingmentioning
confidence: 99%
“…Maud Fagny and colleagues have suggested that populations can initially respond to environmental challenges via epigenetic changes, uncoupled from variation in the DNA sequence, with the adaptive phenotype increasingly being achieved via genetic changes as time passes. (61) It has also been suggested that epigenetic changes may account for the missing heritability determinants of complex diseases, such as atherosclerosis, hypertension, metabolic syndrome, and diabetes. (42)(43)(44)(45)62) Hyperhomocysteinemia in atherosclerosis is perhaps one of the mechanisms of the phenomenon of total DNA hypomethylation, characterizing, apparently, both the onset and progression of the disease.…”
Section: Epigenetic Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…He is also interested in the degree of genetic and epigenetic variation in the human population, and analyzed SNP data and genome-wide DNA methylation at 450,000 sites in various African populations. He showed that historical lifestyle affects DNA methylation under genetic control at genes associated with development, such as bone density and height, whereas methylation variation associated with recent changes in habitat prominently affects loci involved in immune processes (Fagny et al, 2015). As Michael Snyder (Stanford University, USA) showed in his talk about personal ʻomics' data analyses for managing and predicting diseases, these integrative approaches -using population genetics, functional genomics and big data relating to human lifestyles -represent a powerful means to understand (epi)genotype-phenotype correlations and mechanisms of adaptation/response to environmental stresses.…”
Section: Human Evolutionmentioning
confidence: 99%
“…Although direct approaches based on bisulfite sequencing [154,155] and enrichment of methylated epialleles [73] have been used, the most successful approach currently available leverages on aDNA damage patterns to computationally derive genome-wide cytosine methylation and nucleosome maps [8,152,156]. Interestingly, lifestyle and socio-cultural differences are known to influence such epigenetic signatures in contemporary human groups [157]. Their persistence in aDNA molecules paves the way for an investigation of how epigenetic profiles might have been modified during major human evolutionary transitions, such as the Neolithic and the Industrial Revolution [158].…”
Section: Perspectivesmentioning
confidence: 99%